Review Paper on Various Data Hiding Techniques (International Journal of Engineering and Computer Science, 2015)
The desire to send a message as safely and as securely as possible has been the point of discussion since time immemorial. Information is the wealth of any organization. This makes security-issues top priority to an organization dealing with confidential data. Whatever is the method we choose for the security purpose, the burning concern is the degree of security. Steganography is an art of hiding the secret message in a cover object without leaving a remarkable track on the original message. It is used to increase the security of message sent over the internet. In contrast to cryptography, it is not used to scramble the data but it is used to conceal the data in digital media. Thus, this paper reviews various data hiding techniques and briefly explain Steganography.